Idiomatic Expression Found in Movie Script the Beauty and the Beast: Semantic Study - Ilmi Fadillah; Puspita Sari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This research aims to determine the types of idiomatic expressions and to identify patterns of idiomatic expressions in the movie script The Beauty and The Beast. The theories to analyze the types and the patterns are taken from O'Dell & McCarthy's (2017) and Joodi's (2012). This research uses the descriptive qualitative method. In collecting data, this research used the forms of classification, documentation, and monolingual dictionaries. After analyzing the data, it is found that there are 30 data divided into 20 data of fixed statements (66,67%), 5 data of slang (16,67%), 3 data of proverbs (10%), and 2 data of clichés (6,66%). It can be identified some idiomatic expression patterns used in The Beauty and The Beast movie script such as noun phrases, transitive verb phrases, verbal phrases, prepositional phrases, word pairs, and pattern sentences. The type of idiomatic expression that is the most dominant and often appears in the script of The Beauty and The Beast is fixed statements.